Ferroptosis: A Specific Vulnerability of RAS-Driven Cancers? - Andreani, Cristina; Bartolacci, Caterina; Scaglioni, Pier Paolo (Frontiers in Oncology, 2022)
Ferroptosis has emerged as a new type of programmed cell death that can be harnessed for cancer therapy. The concept of ferroptosis was for the first time proposed in in the early 2000s, as an iron-dependent mode of regulated cell death caused by unrestricted lipid peroxidation (LPO) and subsequent plasma membrane rupture. Since the discovery and characterization of ferroptosis, a wealth of research has improved our understanding of the main pathways regulating this process, leading to both the repurposing and the development of small molecules. However, ferroptosis is still little understood and several aspects remain to be investigated. For instance, it is unclear whether specific oncogenes, cells of origin or tumor niches impose specific susceptibility/resistance to ferroptosis or if there are some ferroptosis-related genes that may be used as bona fide pan-cancer targetable dependencies. In this context, even though RAS-driven cancer cell lines seemed to be selectively sensitive to ferroptosis inducers, subsequent studies have questioned these results, indicating that in some cases mutant RAS is necessary, but not sufficient to induce ferroptosis. In this perspective, based on publicly available genomic screening data and the literature, we discuss the relationship between RAS-mutation and ferroptosis susceptibility in cancer.